THE EFFECT OF ORGANIZATIONAL COMPETENCE, MOTIVATION, AND COMMITMENT ON JOB SATISFACTION AND PERFORMANCE OF MEMBERS OF REGENCY/CITY DPRD IN SOUTH SULAWESI PROVINCE - Hengky Yasing; Jeni Kamase; Achmad Gani; Amir Amir; Mashur Razak (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to 1) To analyze the direct influence of competence, motivation and organizational commitment on satisfaction and performance. 2) To analyze the indirect effect of competence, motivation and organizational commitment on performance through job satisfaction. This study uses a quantitative approach by using primary data through a questionnaire of as many as 268 respondents with a population of 815. The study was conducted from July to September 2022. The data were analyzed using the Structural Equating Modeling program SPSS V. 25 and Amos v 25. The results of this study indicate that: (1) competence has a positive and significant effect on job satisfaction. (2) motivation has a positive and not significant effect on job satisfaction. (3) organizational commitment has a positive and significant effect on job satisfaction (4) job satisfaction has a positive and significant effect on performance (5) competence has a positive and insignificant effect on performance (6) motivation positive and significant effect on performance. (7) organizational commitment has a positive and insignificant effect on performance.